Theological Perspectives for Life, Liberty, and the Pursuit of Happiness
XXVIII, 184 p.
Keywords: Rather than wield religion as a weapon or a ruse in irrational appeals, the book attempts to reimagine a shared American mythos and ethos, by reminding us of our shared stake in creating an America committed to the life of all peoples and species and to the full developments of our capabilities as an exercise of liberty.